Analisis Komparatif Academic Bouyancy Ditinjau dari Gender dan Status Pekerjaan Mahasiswa - Arung Samudera (Fakultas Agama Islam Universitas Muhammadiyah Palembang, 2026)
This study aims to analyze the differences in academic buoyancy between working and unemployed students, and to examine the differences of gender and age on academic buoyancy. Academic buoyancy is defined as a student's ability to survive and overcome daily academic obstacles. Using a quantitative method with a comparative approach, this study involved 128 active students (64 working and unemployed students each) who were selected by random sampling. Data were collected using the Academic Buoyancy scale developed by Martin & Marsh (2008), covering 5 aspects (Confidence, Coordination, Composure, Commitment, and Control). Data analysis was carried out using the Pearson Product Moment validity test, Cronbach's Alpha reliability, Kolmogorov-Smirnov and Shapiro-Wilk normality, and the Independent Sample T-Test. The results showed that there were significant differences in academic buoyancy between working and unemployed students, where working students had higher average scores on the aspects of confidence, coordination, commitment, and control. This indicates that work experience can improve students' ability to manage stress, build self-confidence, and regulate commitment and self-control in an academic context. However, the difference in the composure aspect is not very significant. Furthermore, significant differences in academic buoyancy based on gender were found in confidence and commitment, with male students showing higher score, while cordination, composure, and control showed no differences at all between men and women.